Substrates, emergence and initial development of passion fruit seedlings - Paixão, Marcus Vinicius Sandoval; Denardi, Breno Emilio Fernandes; Faian, Mariele Stinghel; Nandorf, Rodrigo Junior; Felisberto, Rudson Tonoli (Comunicata Scientiae, 2021)
The propagation of any crop is understood as a crucial step for the success of the crop, being the main form of propagation of passion fruit to sexual, where almost all cases of commercial plantations, orchards are formed from seedlings generated from seeds produced in substrates. The objective was then to evaluate the effect of different substrates on the emergence and initial development of passion fruit (Passiflora edulis) seedlings. The experimental design was a randomized block with 6 treatments and 4 repetitions with 25 seeds per experimental unit. The seeds were submitted to the treatments, sown in different substrates, being: T1 = Pure soil (100%); T2 = Soil (75%) + humus (25%); T3 = Soil (75%) + bovine manure (25%); T4 = Soil (75%) + chicken manure (25%); T5 = Soil (75%) + Natufert® organomineral fertilizer (25%); T6 = Soil (75%) + coffee straw (25%). Thirty days after sowing the variables were evaluated, percentage of germination. Sixty days after sowing were evaluated: number of leaves; plant height; collection diameter; root length; leaf green mass; leaf dry mass; green root mass; dry root mass. The treatment Terra (75%) + coffee straw (25%) proved to be the most recommended with regard to variables of the aerial part, while Terra (75%) + humus (25%) and Terra (75%) + bovine manure (25%) were the most suitable for the root development of seedlings.